Long-Term Rupture Risk in Patients with Unruptured Intracranial Aneurysms Treated with Endovascular Therapy: A Systematic Review and Meta-Analysis - Rizvi, A.; Seyedsaadat, S.M.; Alzuabi, M.; Murad, M.H.; Kadirvel, R.; Brinjikji, W.; Kallmes, D.F. (American Journal of Neuroradiology, 2020)
BACKGROUND: Surveillance imaging of previously unruptured, coiled aneurysms remains routine even though reports of rupture of these aneurysms are extremely rare.PURPOSE: We performed meta-analysis to examine long-term rupture risk over ≥1-year follow-up duration in patients with unruptured intracranial aneurysm who underwent endovascular therapy.DATA SOURCES: Multiple databases were searched for relevant publications between 1995 and 2018.STUDY SELECTION: Studies reporting outcome of long-term rupture risk over ≥1-year follow-up in treated patients with unruptured intracranial aneurysms were included.DATA ANALYSIS: Random effects meta-analysis was used, and results were expressed as long-term rupture rate per 100 patient-year with respective 95% CIs. For ruptured aneurysms during follow-up, data were collected on size and completeness of initial Treatment.DATA SYNTHESIS: Twenty-four studies were identified. Among 4842 patients with a mean follow-up duration of 3.2 years, a total of 12 patients (0.25%) experienced rupture of previous unruptured intracranial aneurysms after endovascular treatment. Nine of these 12 patients harbored aneurysms that were large, incompletely treated, or both. A total of 2 anterior circulation, small, completely coiled aneurysms subsequently ruptured. The long-term rupture rate per 100 patient-year for unruptured intracranial aneurysms treated with endovascular therapy was 0.48 (95% CI, 0.45–0.51). Retreatment was carried out in 236 (4.9%) of these 4842 patients.LIMITATIONS: A limitation of the study is that a lack of systematic nature of follow-up and mean follow-up duration of 3.2 years are not sufficient to make general recommendations about aneurysm followup paradigms.CONCLUSIONS: Given a 5% retreatment rate, postcoil embolization spontaneous rupture of previously unruptured, small- and medium-sized, well-treated aneurysms is exceedingly rare.CIconfidence intervalPRISMAPreferred Reporting Items for Systematic Reviews and Meta-AnalysesPYpatient-yearUIAunruptured intracranial aneurysm